Persepsi Siswa Terhadap Kompetensi Calon Guru Matematika Pada Praktik Magang Blended Learning - Wachid Nugroho (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2022)
Along with the easing of the covid-19 pandemic situation, learning is held directly using a blended learning model. A mathematic teacher candidate is required to be able to adapt to the development of learning conditions before actually becoming a professional teacher with superior competence. This study aims to describe student’s perceptions of the competence of mathematic teacher candidate in the practice of blended learning internships. The qualitative description approach in this research analyzed 68 student respondents in the first semester of 2021-2022 at one of vocational high school in Salatiga. The results showed that students’ perceptions of the competence of mathematic teacher candidate were in the very good category in the four aspects of pedagogic competence, namely mastery of student characteristics, educational learning activities, potential development, and communication with students. Likewise for aspects of personality competence or exemplary, social attitude competence, and professional competence or material mastery at very good category level. Careful preparation and planning focus with no other workloads during and before teaching only to two practical classes will have different implementations later when actually become a mathematic teacher.